2006
DOI: 10.1073/pnas.0602607103
|View full text |Cite
|
Sign up to set email alerts
|

Runaway domain swapping in amyloid-like fibrils of T7 endonuclease I

Abstract: Amyloid fibrils are associated with >20 fatal human disorders, including Alzheimer's, Parkinson's, and prion diseases. Knowledge of how soluble proteins assemble into amyloid fibrils remains elusive despite its potential usefulness for developing diagnostics and therapeutics. In at least some fibrils, runaway domain swapping has been proposed as a possible mechanism for fibril formation. In runaway domain swapping, each protein molecule swaps a domain into the complementary domain of the adjacent molecule alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 44 publications
3
97
0
1
Order By: Relevance
“…To create contact, and thus binding energy between the two wrapped protofilaments, we introduce runaway domain swapping interactions that join the two protofilaments at the seams created by the protofilament edges. Runaway swapping interactions have been observed in fiber assembly (37)(38)(39). A TABFO model with runaway domain swapping is shown schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To create contact, and thus binding energy between the two wrapped protofilaments, we introduce runaway domain swapping interactions that join the two protofilaments at the seams created by the protofilament edges. Runaway swapping interactions have been observed in fiber assembly (37)(38)(39). A TABFO model with runaway domain swapping is shown schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The creation of higher order oligomers through domain swapping has been found to play multiple roles in vivo. Domain-swapped proteins have been shown to form amyloid-like fibrils, 38 which has led to the proposal that deposition diseases that involve protein aggregation, e.g. Alzheimer's and Parkinson's, may involve runaway domain swapping.…”
Section: Discussionmentioning
confidence: 99%
“…1C) (10,15,22,27,44). A recent study of in vitro fibrillization of a variant of T7 endonuclease has provided experimental evidence of propagated domain swapping as a mechanism in the formation of amyloid-like fibrils (25). To investigate a possible role of propagated three-dimensional domain swapping in the formation of cystatin C oligomers, redox experiments have been performed using stabilized wt cystatin C variants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the process of three-dimensional domain swapping, when propagated in an open-ended fashion, could be the basis of the formation of amyloid fibrils (22)(23)(24)(25)(26)(27). We have earlier reported on stabilized variants of monomeric wt and L68Q cystatin C, with cysteine mutations introduced for selective formation of disulfide bridges between the tertiary structure elements that undergo separation on domain swapping (Fig.…”
mentioning
confidence: 99%